Forever changes [a novel] - Halpin, Brendan 1968- (Farrar Straus Giroux, 2008)
Although encouraged to apply to colleges, Brianna Pelletier, a mathematically-gifted high school senior with cystic fibrosis, dwells on her mortality and the unfairness of life